An exploration of Latine experiences of school and college readiness during the COVID-19 pandemic: a LatCrit and cultural wealth perspective - Joachin, Vanessa S., author; Conner, Bradley, advisor; Fisher, Gwen, committee member; Chavez, Ernest, committee member; Riggs, Nathaniel, committee member (Colorado State University. Libraries, 2022)
Marginalized communities, including Latine people, have historically been denied access to post-secondary education. This is not surprising when one considers that U.S. institutions of education were not conceived for People of Color. While enrollment trends for Latine college-bound students are promising, disparities persist. Latine communities still have higher rates of school attrition than non-Latine populations and the increase in high school graduation and college enrollment still lags non-Latine communities. While LatCrit and Community Cultural Wealth literature provide a valuable and comprehensive approach to understanding the experience of Communities of Color, cultural and social capital scholarship and deficiency thinking continue to be prevalent in current Latine education and college preparation research. Most research places the dominant (school or program) narrative at the center of studies. Additionally, COVID-19 brought national concern and discourse around accessible childcare, student health, and education loss as well as the exacerbated inequity in these domains on low-income and BIPOC students and families. Given that systematically created education gaps have always existed and disproportionately hurt BIPOC communities, it is important to understand the impact of COVID-19 on those established gaps, how BIPOC students and families navigate school during the pandemic, and how communities and institutions are supportive or hostile toward BIPOC students in their pursuit of education. This study used Interpretive Phenomenological Analysis informed by LatCrit and Community Cultural Wealth frameworks to explore (a) how the pandemic has impacted the lives of Latine high school students, their families, and their communities (b) how the negative effects of the pandemic connect to systemic and historical oppression of the Latine community (c) the students' use of intrapersonal and community strengths to navigate school and post-school plans during the pandemic. The sample of Latine 11th and 12th grade students were predominantly low-income and self-identified as Latine. Data was analyzed by coding for meaning units and themes. Themes were organized using Nvivo software.
Keywords: community cultural wealth; critical race theory; college readiness; high school sutdents; COVID-19